Bráðaofnæmi í tveimur landbúnaðarhéruðum á Íslandi : II. Samband heyverkunaraðferða og einkenna af heyryki - Davíð Gíslason; Tryggvi Ásmundsson; Vigfús Magnússon; Gravesen, Suzanne (Læknafélag Íslands, Læknafélag Reykjavíkur, 2010)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn Skoða/Opna(view/open) Immediate type allergy in two farming communities in Iceland. II. Correlation between hay-making methods and symptoms related to work við forage. The aim of this investigation was to study correlation between haymaking methods and symptoms related to work with forage in two farming communities in Iceland. The difference between those two communities and the methods used including the selection of the study group have been described earlier (Gíslason D et a.: Immediate type allergy in two farming communities in Iceland. I. Prevalence and cause of symptoms. Icelandic Med J, this same issue). The questionnaire included questions about symptoms after work with forage and hay-making methods. In Strandasýsla 88% made >90% of their harvest into sileage, whereas none in V. Skaftafellssýsla did. Of 167 individuals in Strandasýsla, 19% had respiratory or eye symptoms related to work with forage. These symptoms were cough, dyspnea, fever, sneezing spells, nasal or eye discharge or itching. In V. Skaftafellssýsla 24% of 152 individuals had such symptoms. Regular hay, especially moldy hay, correlated best with these symptoms. Sixty individuals correlated their symptoms with some kind of forage, whereas only 5 correlated symptoms with work with silage, even of poor quality. There was no significant difference between the incidence of these symptoms in the two communities. The use of protecting masks was of help to decrease these symptoms. Equipment to help dry hay in the barn and bailing machines were of questionable benefit, and blowers used to blow hay into barns might be harmful. Silage making seems to be the method of choice for individuals with respiratory or eye symptoms after hay dust exposure. Óhætt er að fullyrða að fáar stéttir á íslandi séu í jafn mikilli hættu á að fá atvinnusjúkdóma og bændur. Landbúnaður var aðal atvinnuvegur þjóðarinnar frá upphafi byggðar og fram á þessa öld. Flestir vinnufærir ...